Pluripotent Stem Cell Metabolism and Mitochondria: Beyond ATP - Jarmon G. Lees; David K. Gardner; Alexandra J. Harvey (Stem Cells International)
Metabolism is central to embryonic stem cell (ESC) pluripotency and differentiation, with distinct profiles apparent under different nutrient milieu, and conditions that maintain alternate cell states. The significance of altered nutrient availability, particularly oxygen, and metabolic pathway activity has been highlighted by extensive studies of their impact on preimplantation embryo development, physiology, and viability. ESC similarly modulate their metabolism in response to altered metabolite levels, with changes in nutrient availability shown to have a lasting impact on derived cell identity through the regulation of the epigenetic landscape. Further, the preferential use of glucose and anaplerotic glutamine metabolism serves to not only support cell growth and proliferation but also minimise reactive oxygen species production. However, the perinuclear localisation of spherical, electron-poor mitochondria in ESC is proposed to sustain ESC nuclear-mitochondrial crosstalk and a mitochondrial-H2O2 presence, to facilitate signalling to support self-renewal through the stabilisation of HIFα, a process that may be favoured under physiological oxygen. The environment in which a cell is grown is therefore a critical regulator and determinant of cell fate, with metabolism, and particularly mitochondria, acting as an interface between the environment and the epigenome.